2010
DOI: 10.1111/j.1365-2265.2009.03666.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin and carcinoembryonic antigen doubling times as prognostic factors in medullary thyroid carcinoma: a structured meta‐analysis

Abstract: The dts of both calcitonin and CEA are strong prognostic indicators for MTC recurrence and death. CEA dt has a higher predictive value than calcitonin dt and therefore measuring both tumour markers is essential for proper risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(109 citation statements)
references
References 27 publications
5
99
0
5
Order By: Relevance
“…In agreement with this finding is the The Kaplan-Meier curve of survival in patients with normal and abnormal levels of Ca 19.9. A rapid increase of the Ct and CEA Dt is considered a strong prognostic indicator for MTC recurrence and death, as demonstrated in several studies and metanalyses (16,17,18). This study showed that in our group of advanced MTC, not only the Ct Dt but also abnormal serum levels of Ca 19.9 were prognostic factors of death.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In agreement with this finding is the The Kaplan-Meier curve of survival in patients with normal and abnormal levels of Ca 19.9. A rapid increase of the Ct and CEA Dt is considered a strong prognostic indicator for MTC recurrence and death, as demonstrated in several studies and metanalyses (16,17,18). This study showed that in our group of advanced MTC, not only the Ct Dt but also abnormal serum levels of Ca 19.9 were prognostic factors of death.…”
Section: Discussionmentioning
confidence: 53%
“…In particular, the doubling time (Dt) of both Ct (Ct Dt) and CEA is a strong prognostic indicator for MTC recurrence and death (15,16,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…For the time being, the clinician's only effective tools for gauging the progressive or stable nature of a case of MTC are Ct and carcinoembryonic antigen (CEA) doubling times during the follow-up (19,20). Several studies have attempted to find novel molecular markers capable of identifying the more aggressive MTC with a view to planning appropriate surgery and a tailored patient follow-up right from the start.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with normal levels of tumor markers and imaging after surgery should be followed up annually and those with persistent tumor markers should be observed more closely. Patients with calcitonin and CEA doubling time within 6 months have a shorter overall survival time [107]. …”
mentioning
confidence: 99%